Effect of o-Cresol, Resorcinol and Hydroquinone on Citric Acid Productivity by Aspergillus niger in Stirred Fermentor - SITKI ÇEVRIMLI*, BEKIR; YASAR†, AHMET; KARIPTAS‡, ERGIN (Asian Journal of Chemistry, 2009)
Effects of o-cresol, resorcinol and hydroquinone, which are toxicchemicals, on citric acid biosynthesis and biomass in the artificial culturesetting of Aspergillus niger using batch fermenter are examined in themost favourable fermentation conditions and a model is proposed.According to this model, maximum citric acid concentration is 48.3 g L-1in a culture that does not contain any toxic chemicals, whereas the maximumconcentrations obtained in cultures containing 15 mg L-1 o-cresol, 45 mg L-1resorcinol and 35 mg L-1 hydroquinone are 86.7, 82.8 and 86.8 g L-1,respectively. Moreover, addition of toxic chemicals to the culture reducesfermentation time by 24 h.